Empirical Model of Unconsolidated Tephra Erosion: Verification and Application on Micro Catchment - F. Tata Yunita; Indratmo Soekarno; Joko Nugroho; Untung B. Santosa (Civil Engineering Journal, 2024)
Erosion is an important process that shapes the earth's surface. Given the complexity of the process, efforts to understand it are essential. Over the last 50 years, numerous models of soil particle erosion by surface runoff emerged, some of which share similar forms and parameters. The differences lie in the coefficient values of the parameters, attributed to the characteristics of the soil material such as texture, structure, and organic matter content. However, these erosion models tend to underpredict in the case of new volcanic deposit erosion. The erosion model for unconsolidated tephra, proposed by Yunita, was developed through laboratory experiments using volcanic material from Merapi Volcano, Indonesia. Nevertheless, the model has not been implemented for other cases. Therefore, this study aims to verify the erosion model for volcanic material in other cases, explore the possibility of broader implementation, identify the factors that influence its accuracy, and determine the model’s limitations. To verify the model’s potential for broader application, we applied it to micro-scale catchments in St. Hellens (USA), Sakurajima (Japan), and a laboratory scale plot in Merapi (Indonesia). The verification yielded satisfactory results for all three cases, especially for new tephra deposits. In the case of St. Helens, the extrapolation of model coefficients was proven to still be applicable even for thicker tephra layers. However, the erosion prediction was overestimated for tephra layer deposits older than 1 year, as the erosion rate decreases over time due to the compaction and stabilization of the tephra layer. In the Sakurajima, the model was also suitable for predicting long-term erosion amounts (daily and monthly). Meanwhile, in Merapi, the model provided accurate predictions for slopes of 20º and 25º but was less accurate for 30º slopes, where the measured erosion was due to both erosion and slope failure. These verification results demonstrate the potential of applying the empirical erosion model to micro catchments with relatively homogenous slopes and tephra properties. The sensitivity test revealed that slope, runoff, rainfall intensity, and volcanic ash thickness are strongly influence the erosion rate. This study also simplified the volcanic ash erosion model as a function of slope (S0), runoff (q), and rainfall (i) by assuming the value of (1-τc/τ0) is equal to 1. Further study using GIS tools is required for its application on several catchments with heterogeneous characteristics. Doi: 10.28991/CEJ-2024-010-07-02 Full Text: PDF